Preventing harm: A balance measure for improving the detection of fetal growth restriction. (26th March 2021) - Selvaratnam, Roshan J.; Wallace, Euan M.; Hunt, Rodney W.; Davey, Mary‐Ann
Abstract : Background: Increasing the detection of fetal growth restriction (FGR), while reducing stillbirth, also leads to unnecessary early intervention, and associated morbidity, for normally grown babies who are incorrectly suspected of FGR. Aims: We sought to design a balance measure that addresses the specificity of FGR detection. Methods: A retrospective cohort study on all singleton births ≥32 weeks gestation in 2016 and 2017 in Victoria. We compared two balance measures for the detection of FGR, defined as the proportion of all babies iatrogenically delivered before 39 weeks gestation for suspected FGR that had a birthweight ≥10th centile (balance measure 1) or ≥25th centile (balance measure 2). Hospital level performance on each balance measure was derived and compared to an existing performance measure for severe FGR detection in Victoria. Results: Of the 38 hospitals analysed, 12 (32%) had a favourable performance on an existing indicator of FGR detection, seven (18%) hospitals had a favourable performance on balance measure 1, and 15 (39%) had a favourable performance on balance measure 2. There was a moderate correlation between hospital performance on the existing indicator and on balance measure 1 ( r = 0.447, P = 0.005) but not balance measure 2 ( r = −0.063, P = 0.71). There was no difference in perinatal mortality between high performing hospitals and low performing hospitals. Conclusion: Introducing a balance measure into routine reporting may bring greater awareness to the unintended harm associated with increased detection of FGR.